The Continental Dimension of Modern Montreal - France Vanlaethem (Docomomo Journal, 2022)
Aspiring to mobility is a component of modernity and of the ideology underpinning the modern movement in architecture. This value determines the unstable relationship modern man has with land, while belief in progress has guided his futuristic notion on time. It accounts for the transportation revolution that occurred almost two hundred years ago with the advent of mechanized locomotion.